Microstructural analysis and reliability of monolithic zirconia after simulated adjustment protocols - Chun, Eliseo Pablo [UNESP]; Anami, Lilian Costa [UNESP]; Bonfante, Estevam Augusto; Bottino, Marco Antonio [UNESP] (Elsevier, 2017)
Objective To investigate the microstructural properties and reliability of zirconia partially stabilized by yttrium oxide (Y-TZP) for use in monolithic form (Vita YZ HT, Vita Zahnfabrik, Germany) after different clinical adjustment protocols simulation. One-hundred and sixty two Y-TZP discs of high translucency were divided into 6 groups (n = 27), according to simulated adjustments: S-Y-TZP as sintered; G-glazed Y-TZP; DbG-Y-TZP with diamond bur adjustment simulation followed by glaze application; GDb-glazed Y-TZP adjusted with diamond bur; DbDrG-Y-TZP with adjustment simulation with diamond bur and polishing kit (diamond rubber), followed by glaze; GDbDr-glazed Y-TZP with adjustment simulation with diamond bur followed by polishing kit. Methods After monotonic testing under biaxial flexure (n = 3), remaining specimens were distributed into 3:2:3 ratio and tested under step-stress accelerated life testing. Specimens were evaluated in a stereomicroscope and SEM. Microstructure was analyzed by X-ray diffraction and mean surface roughness (Ra). Survival data were used to calculate Weibull's beta value (β) and reliability for missions of 300,000 and 600,000 cycles at 200 N. Ra data were statistically analyzed by 1-way ANOVA and Tukey's test (both, a = 5%). Results The untreated HT zirconia (S) presented a lower probability of survival after 600,000 cycles at 200 N, compared to HT zirconia adjusted with diamond bur and glazed (DbG), and after final polishing with polishing kit (GDbDr). Final polishing with diamond rubber (GDbDr) resulted in a more homogeneous surface compared to glazed samples (G, DbG and DbDrG). Significance HT zirconia is more likely to present increased survival when glazed after diamond adjustments (DbG) or when it is finished with polishing kit (GDbDr).
Keywords: Mechanical stress; Prosthesis fitting; Zirconium